Arterial Stiffness and Blood Pressure in Patients Newly Diagnosed with Graves' Disease Compared with Euthyroid Controls. Issue 3 (14th May 2020) - Grove-Laugesen, Diana; Malmstroem, Sofie; Ebbehoj, Eva; Riis, Anne Lene; Watt, Torquil; Rejnmark, Lars; Würgler Hansen, Klavs
Abstract : Introduction and Objective: The excess cardiovascular morbidity and mortality in hyperthyroidism and Graves' disease (GD) is inadequately understood. We aimed to elucidate whether well-established cardiovascular risk factors such as arterial stiffness in terms of pulse wave velocity (PWV) and blood pressure differ in GD and controls. Methods: This was a cross-sectional study comparing 55 hyperthyroid patients with newly diagnosed GD and 55 euthyroid, population-based controls matched for age, sex and menopausal status. PWV and blood pressure were measured in office (SphygmoCor Xcel) and 24-h ambulatory settings (Arteriograph). Differences between groups were assessed using adjusted linear regression analysis. Results: Compared to controls, GD patients showed higher PWV in the 24-h but not in the office setting with an adjusted 24-h PWV difference of 1.0 (95% CI: 0.6–1.5) m/s. PWV was higher in GD at both day and night, and nightly PWV dipping was lower (–5.5, 95% CI: –10.4 to –0.6%). Furthermore, central and brachial pulse pressure was significantly higher in both the office and 24-h setting, whereas nightly central pulse pressure dipping was significantly lower in GD (–5.4, 95% CI: –10.5 to –0.2%). Mean arterial pressure did not differ between the groups. Conclusions: Despite comparable blood pressure, GD is associated with a higher 24-h PWV that was not detected in the office setting. Pulse pressure was higher in GD, whereas mean arterial pressure did not differ between the groups. Longitudinal studies should pursue whether higher PWV might be a piece to the puzzle of understanding the increased risk of cardiovascular disease in hyperthyroidism and GD.